Magic Johnson : hero on and off court - Gutman, Bill. (Brookfield, Conn. : Millbrook Press, 1992)
Examines Magic Johnson$1 (Bs career as a record-breaking champion with the L.A. Lakers and discusses his fight against AIDS.s
"A Millbrook Press library edition"--P. [4] of cover.
Includes bibliographical references (p. [46]) and index.
Keywords: Johnson, Earvin, -- 1959- -- Juvenile literature; Johnson, Earvin, -- 1959-; Basketball players -- United States -- Biography -- Juvenile literature; Basketball players; African Americans -- Biography